Role of enzymatic activity inmuscle damage and cytotoxicity induced by Bothrops asper Asp49 phospholipase A2 myotoxins: are there additional effector mechanisms involved? - Mora Obando, Diana (2014)
artículo (arbitrado) -- Universidad de Costa Rica, Instituto de Investigaciones Clodomiro Picado (ICP). 2014